Monitoring For Elemental Composition Of Particulate Matter Deposited In Snow Cover Around Coal-Fired Thermal Power Plant (Karaganda, Central Kazakhstan); Geography, Environment, Sustainability; Vol. 16, No. 4 - Talovskaya A. V. Anna Valerievna (2023, 2023)
Title screen